2006
DOI: 10.1103/physrevd.74.023004
|View full text |Cite
|
Sign up to set email alerts
|

Observational constraints on self-accelerating cosmology

Abstract: The DGP brane-world model provides a simple alternative to the standard LCDM cosmology, with the same number of parameters. There is no dark energy -the late universe self-accelerates due to an infrared modification of gravity. We compute the joint constraints on the DGP model from supernovae, the cosmic microwave background shift parameter, and the baryon oscillation peak in the SDSS luminous red galaxy sample. Flat DGP models are within the joint 2 sigma contour, but the LCDM model provides a significantly b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
182
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(191 citation statements)
references
References 23 publications
8
182
1
Order By: Relevance
“…To constrain the parameters of model we fit our model with the new Gold sample and SNLS supernova data, CMB shift parameter, position of the first and third peaks of power spectrum of temperature fluctuations at the last scattering surface, the Cluster Baryon Gas Mass Fraction, location of baryonic acoustic oscillation peak observed by SDSS and large scale structure formation data by 2dFGRS. The best parameters obtained from fitting with the new Gold sample data are: h = 0.62, Ωm = 0.28 +0.03 −0.02 , Ωr c = 0.13 +0.01 −0.01 and Ω K = −0.002 +0.064 −0.053 at 1σ confidence level with [26,31] showed that large scale structure observations from 2dFGRS experiment had weak effect on confining the acceptance intervals for the free parameters. The observational constraint just by using SNIa+CMB indicated that our universe is spatially open but combining these result with SDSS+gas+LSS showed that our universe in the DGP model is very good agreement with the spatially flat universe.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To constrain the parameters of model we fit our model with the new Gold sample and SNLS supernova data, CMB shift parameter, position of the first and third peaks of power spectrum of temperature fluctuations at the last scattering surface, the Cluster Baryon Gas Mass Fraction, location of baryonic acoustic oscillation peak observed by SDSS and large scale structure formation data by 2dFGRS. The best parameters obtained from fitting with the new Gold sample data are: h = 0.62, Ωm = 0.28 +0.03 −0.02 , Ωr c = 0.13 +0.01 −0.01 and Ω K = −0.002 +0.064 −0.053 at 1σ confidence level with [26,31] showed that large scale structure observations from 2dFGRS experiment had weak effect on confining the acceptance intervals for the free parameters. The observational constraint just by using SNIa+CMB indicated that our universe is spatially open but combining these result with SDSS+gas+LSS showed that our universe in the DGP model is very good agreement with the spatially flat universe.…”
Section: Resultsmentioning
confidence: 99%
“…For the Likelihood analysis we use some weak priors for the model parameters indicated in Table 1. The best values for the parameters of the model [26] and [31]. In the first reference they report the following values for the model parameters: Ωm = 0.34 +0.07 −0.08 and Ωr c = 0.24 +0.04 −0.04 using old SNIa Gold sample while in the second reference Marteens et.…”
Section: Observational Constraints From the Background Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…The shift parameter encapsulates information contained in the detailed CMB power spectrum and, more importantly, its measured values is weakly dependent of assumptions made about dark energy. It has been used recently to put constraints on models with braneworld cosmologies [36]. The shift parameter R is defined by…”
Section: A Constant Equation Of Statementioning
confidence: 99%
“…The influence of this modification of the growth factor on lensing observables was recently studied in Ref. [75]. From these definitions, we deduce that in the DGP-4D case, the equation of evolution of the growth factor (21) can be rewritten in terms of the growth variable, g ≡ D/a, as…”
Section: Growth Of Density Perturbationmentioning
confidence: 92%